(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article examines the vital role of lab technicians in enhancing quality assurance for nurses by ensuring accurate test results in healthcare settings. Accurate test results are crucial for guiding clinical decisions and patient care, making the collaboration between lab technicians and nurses indispensable. Lab technicians contribute to quality assurance through meticulous specimen handling, instrument calibration, and validation of testing methodologies. They also play a key role in troubleshooting discrepancies and providing valuable insights into result interpretation. Collaboration between lab technicians and nurses fosters a culture of interdisciplinary teamwork, promoting optimal patient outcomes.